B-Site Cation Ordered Double Perovskites as Efficient and Stable Electrocatalysts for Oxygen Evolution Reaction - Sun, H.; Chen, G.; Zhu, Y.; Liu, B.; Zhou, W.; Shao, Zongping (Wiley - V C H Verlag GmbH & Co. KGaA, 2017)
Simple disordered perovskite oxides have been intensively exploited as promising electrocatalysts for the oxygen evolution reaction (OER) towards their application in water splitting, reversible fuel cells, and rechargeable metal-air batteries. Here, the B-site cation-ordered double perovskites Ba2BixSc0.2Co1.8-xO6-d, with two types of cobalt local environments, are demonstrated to be superior electrocatalysts for OER in alkaline solution, demonstrating ultrahigh catalytic activity. In addition, no obvious performance degradation is observed for the Ba2Bi0.1Sc0.2Co1.7O6-d sample after a continuous chronopotentiometry test. The critical role of the ordered [Co2+] and [Sc3+, Bi5+, Co3+] dual environments in improving OER activity is exhibited. These results indicate that B-site cation-ordered double perovskite oxides may represent a new class of promising electrocatalysts for the OER in sustainable energy storage and conversion systems.